1980
DOI: 10.1007/bf00421857
|View full text |Cite
|
Sign up to set email alerts
|

Insulin antibodies prevent insulin-receptor interactions

Abstract: Summary. The study was carried out to investigate whether insulin bound to antibody is able to bind the insulin receptor of target tissues. Three specific rabbit anti-insulin sera as well as sera from eight diabetic patients with insulin antibodies were incubated, free of insulin, with labelled insulin for 48 h at 4 ~ following incubation labelled insulin was employed in binding experiments on monocytes, erythrocytes and placenta membranes. Using rabbit sera, receptor binding was absent when insulin was totall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…The relationship between the two variables is of the same order as the reduction seen on initial transfer to purified insulins. Studies in vitro have demonstrated the ability of insulin antibody to block insulin: insulin receptor interaction [18]. The results of the present study are compatible with this idea.…”
Section: Discussionsupporting
confidence: 89%
“…The relationship between the two variables is of the same order as the reduction seen on initial transfer to purified insulins. Studies in vitro have demonstrated the ability of insulin antibody to block insulin: insulin receptor interaction [18]. The results of the present study are compatible with this idea.…”
Section: Discussionsupporting
confidence: 89%
“…As already reported, AIA do influence metabolic control [31][32][33][34][35] particularly postprandial blood glucose. Some authors [9] found no direct correlation between the AIA levels and glycaemic control, nor did we.…”
Section: Discussionsupporting
confidence: 65%
“…In conclusion, contradictory results of different authors (Shechter et al, 1979 a;De Pirro et al, 1980) with respect to the influence of insulin antibodies on receptor binding may possibly be due to the different size of insulin-antibody complexes formed with different antibodies. Our results support the hypothesis that receptor aggregation via insulin crosslinking is involved in the mechanism of the expression of insulin bioactivity (Jeffrey, 1982).…”
Section: Discussionmentioning
confidence: 82%